2002
DOI: 10.1086/344584
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Hubble Space Telescope[/ITAL] Evidence for an Intermediate-Mass Black Hole in the Globular Cluster M15. II. Kinematic Analysis and Dynamical Modeling

Abstract: We have used the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope (HST) to obtain high spatial resolution spectroscopy of the central region of the dense globular cluster M15. The observational strategy and data reduction were described in Paper I (van der Marel et al. 2002). Here we analyze the extracted spectra with a cross-correlation technique to determine the line-of-sight velocities of individual stars. Our final STIS velocity sample contains 64 stars, two-thirds of which have th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
296
3
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(318 citation statements)
references
References 68 publications
17
296
3
2
Order By: Relevance
“…For example, Gerssen et al (2002) found in their study of M 15 that the necessity for a black hole was diminished when a varying M/L was assumed, which in this case was obtained from FokkerPlanck simulations. These simulations predicted a rise in the central M/L, mainly caused by the segregation of stellar remnants near the centre.…”
Section: Jeans Modellingmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Gerssen et al (2002) found in their study of M 15 that the necessity for a black hole was diminished when a varying M/L was assumed, which in this case was obtained from FokkerPlanck simulations. These simulations predicted a rise in the central M/L, mainly caused by the segregation of stellar remnants near the centre.…”
Section: Jeans Modellingmentioning
confidence: 96%
“…To compare the model predictions of the velocity dispersion to our measurements, we used the same maximum-likelihood approach as in Gerssen et al (2002) and Kamann et al (2014). This approach has the advantage that it does not require any binning of the data.…”
Section: Jeans Modellingmentioning
confidence: 99%
“…However, recent observations (e.g. Gebhardt et al 2000;Gerssen et al 2002;Gebhardt et al 2005;Noyola et al 2008;Lützgendorf et al 2011) have shown that the velocity-dispersion profiles of some globular clusters and dwarf galaxies are consistent with hosting a massive black hole at their center.…”
Section: Introductionmentioning
confidence: 99%
“…DATA Gerssen et al (2002) present radial velocities of 64 stars obtained by the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope (HST ). This sample of stars is characterized by very high spatial resolution; the smallest radius at which kinematic information is available in the sample (r min ) is only about 0.01 pc.…”
Section: Introductionmentioning
confidence: 99%